Using milk leukocyte differentials for diagnosis of subclinical bovine mastitis. Issue 3 (27th June 2017) - Gonçalves, Juliano Leonel; Lyman, Roberta L.; Hockett, Mitchell; Rodriguez, Rudy; dos Santos, Marcos Veiga; Anderson, Kevin L.
Abstract : This research study aimed to evaluate the use of the milk leukocyte differential (MLD) to: (a) identify quarter milks that are culture-positive; and (b) characterize the milk leukocyte responses to specific groups of pathogens causing subclinical mastitis. The MLD measures the absolute number and relative percentage of inflammatory cells in milk samples. Using the MLD in two dairy herds (170 and 172 lactating cows, respectively), we studied all lactating cows with a most recent monthly Dairy Herd Improvement Association somatic cell count (SCC) >200 × 10 3 cells/ml. Quarter milk samples from 78 cows meeting study criteria were analysed by MLD and aseptically collected milk samples were subjected to microbiological culture (MC). Based upon automated instrument evaluation of the number and percentage of inflammatory cells in milk, samples were designated as either MLD-positive or – negative for subclinicial mastitis. Positive MC were obtained from 102/156 (65·4%) of MLD-positive milk samples, and 28/135 (20·7%) of MLD-negative milk samples were MC-positive. When MC was considered the gold standard for mastitis diagnosis, the calculated diagnostic Se of the MLD was 65·4% (IC95% = 57·4 to 72·8%) and the Sp was 79·3% (IC95% = 71·4 to 85·7%). Quarter milks positive on MC had higher absolute numbers of neutrophils, lymphocytes and macrophages, with higher neutrophils% and lymphocytes% but lower macrophages%. The Log10 (N/L) ratios were the most useful ratio to differentiate specific subclinical mastitis quarters from healthy quarters. Use of the MLD on cows with monthly composite SCC > 200 × 10 3 cells/ml for screening at quarter level identified quarters more likely to be culture-positive. In conclusion, the MLD can provide an analysis of mammary quarter status more detailed than provided by SCC alone; however, the MLD response to subclinical mastitis was not found useful to specifically identify the causative pathogen.